2022
DOI: 10.1108/whatt-10-2022-0116
|View full text |Cite
|
Sign up to set email alerts
|

The role of artificial intelligence and blockchain technologies in sustainable tourism in the Middle East

Abstract: PurposeThis paper reviews the role of two significant smart technologies, artificial intelligence (AI) and blockchain technology (BT) in achieving sustainable tourism success. Such changes will maintain consistent tourism growth in the Middle East and North Africa (MENA) region by improving environmental, social and economic sustainability.Design/methodology/approachThis study uses a qualitative approach focusing on AI and blockchain-based adaptations towards sustainability in technology-driven platforms, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Yoo and Kang (2021) observed that self-efficacy in the use of smart technology exerted a positive moderating impact on the central hypothesized route, but a negative moderating impact on three remote routes for the tourism sector. Similarly, the results of our research combined with earlier studies prove that AI and blockchain technology improve the situation of all stakeholders (Kashem et al ., 2022). These conditions in turn promote economic growth that at the same time contributes to sustainable environmental management.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Yoo and Kang (2021) observed that self-efficacy in the use of smart technology exerted a positive moderating impact on the central hypothesized route, but a negative moderating impact on three remote routes for the tourism sector. Similarly, the results of our research combined with earlier studies prove that AI and blockchain technology improve the situation of all stakeholders (Kashem et al ., 2022). These conditions in turn promote economic growth that at the same time contributes to sustainable environmental management.…”
Section: Discussionsupporting
confidence: 87%
“…These conditions in turn promote economic growth that at the same time contributes to sustainable environmental management. Moreover, through introducing green smart technology-driven sustainable tourism principles these technologies can make possible the regeneration of the mass tourism approach that loses its usefulness to the target audience (Kashem et al ., 2022). The findings of Knani et al .…”
Section: Discussionmentioning
confidence: 99%
“…The advent of artificial intelligence (AI) makes this complexity and real-time availability of services somewhat easier. In their article, The role of artificial intelligence and blockchain technologies in sustainable tourism in the Middle East , Kashem et al. (2023) review the role of two significant smart technologies, AI and blockchain technology (BT) in achieving sustainable tourism growth in the Middle East region by improving environmental, social and economic sustainability.…”
Section: Synopsismentioning
confidence: 99%
“…Effective management of the tourism industry can bring many benefits to a country, including increased economic growth and development, job creation, and preservation of cultural and natural heritage [1], [3], [6], [9], [10]. Successful tourism potential management requires a comprehensive understanding of the various factors influencing the industry, including economic, social, cultural, and environmental considerations [11], [12].…”
Section: Introductionmentioning
confidence: 99%